The Application of Burhani Epistemology in the Learning of Aqidah and Akhlak on the Material of Faith in the Last Day to Improve Students' Critical Thinking and Rational Beliefs - Siti Fatimatuzzahro; Irawan Irawan; Erni Haryati Kahfi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Problems in learning Aqidah Akhlak often arise due to the dominance of teacher-centered lecture methods, making students passive and less able to think critically or understand religious teachings rationally. This issue appears clearly in learning the material of faith in the Last Day, which generally emphasizes memorization without providing space for philosophical and rational reasoning. This study aims to apply the principles of Burhani epistemology in learning Aqidah Akhlak on the material of faith in the Last Day to improve students’ critical thinking and rational belief. This research employs a quantitative method with a quasi-experimental design (Static Group Comparison Design), involving two groups: an experimental class using Burhani-based learning and a control class using conventional methods. Data were collected through critical thinking tests and rational belief questionnaires, then analyzed using normality tests, homogeneity tests, and t-tests. The results show that the data are normally distributed (Sig. > 0.05), not homogeneous (Sig. < 0.05), and that there is a significant difference between the two groups (Sig. 0.000 < 0.05). The average score of the experimental class increased to 89.47, while the control class increased to 56.00. Thus, the application of Burhani epistemology is proven effective in enhancing students’ critical thinking and rational belief, as well as integrating reason and revelation harmoniously. This approach is relevant for Aqidah Akhlak instruction to develop logical thinking, strong faith, and scientific morality in students.